2003
DOI: 10.1007/s00520-003-0485-1
|View full text |Cite
|
Sign up to set email alerts
|

The success of data collection in the palliative setting?telephone or clinic follow-up?

Abstract: Assessment of outcomes is essential in order to improve available palliative treatments. Collecting follow-up information can be a challenging task in the palliative setting. We compared the effectiveness of data collection by telephone contact and clinic visit in 112 patients with brain metastases treated with whole-brain radiotherapy. The first 56 patients (group A) were followed by telephone only. The second 56 patients (group B) were asked to attend an outpatient clinic appointment 4 weeks after radiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…This approach decreases the time invested in medical appointments and allows patients to remain in their home communities. The proportion of patients reachable by phone at week 4 (72%) in this study compares favorably with literature reports of 45% [13] and 50% [6]. Follow-up data was unavailable for 94/218 (43%) of patients seen over a 3-year period at another Canadian rapid access clinic, in part due to missed follow-up visits and long travel distances [21].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This approach decreases the time invested in medical appointments and allows patients to remain in their home communities. The proportion of patients reachable by phone at week 4 (72%) in this study compares favorably with literature reports of 45% [13] and 50% [6]. Follow-up data was unavailable for 94/218 (43%) of patients seen over a 3-year period at another Canadian rapid access clinic, in part due to missed follow-up visits and long travel distances [21].…”
Section: Discussionsupporting
confidence: 79%
“…It is unnecessary, and some would say, futile, to require asymptomatic but incurable patients to attend clinic after successful treatment [13]. This is especially true for our patient population who traveled an average of 212 km (round trip) per clinic visit.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Haddad et al compared the effectiveness of data collection by telephone contact and clinic visit in 112 patients with brain metastases treated with whole-brain radiotherapy [3]. The proportion of patients with a successful followup contact at week 4 was 45% and 61%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…However, most studies of patients with brain metastases have shown poorer response rates in follow-up, regardless of whether the assessment is performed by telephone, clinic visit, or by mail. In a study comparing telephone and clinic follow-up, the response rates at week 4 were only 45% for telephone assessment, compared to 61% for clinic assessment [42]. In two studies using either clinic or mail assessments in follow-up, response rates were 45% [43] and 47% [44] at week 4.…”
Section: Discussionmentioning
confidence: 97%